1991
DOI: 10.2105/ajph.81.7.926
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries among North Carolina migrant farmworkers.

Abstract: A population-based cross-sectional study of occupational injuries among a random sample of 287 migrant farmworkers demonstrated frequent obstacles to health care; 65% (11/17) of the more seriously injured subjects did not receive prompt care or never received care. Subjects not receiving prompt care were twice as likely to have incomplete recovery. Employers covered medical expenses for only 5/13 (38%) of the injured workers, and only 3/15 were compensated for lost work. This study indicates that comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…It seems plausible that underreporting of deaths in the rural areas may also be high and therefore a high occupational injury rate may be present in the farming areas. As agriculture is a hazardous occupation with limited worker access to health services and compensation, a need exists for further descriptive research in this area [Myers, 1990;Ciesielski et al, 1991;Chisholm et al, 19921. Internationally, fishing is regarded as a dangerous occupation [Hopper and Dean, 19921. In the case of Cape Town, examination of inquest data for a 5-year period indicated that most fatalities occurred whilst vessels were in the harbor and were due to falls overboard, associated with high blood alchol levels [Lerer LB-unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible that underreporting of deaths in the rural areas may also be high and therefore a high occupational injury rate may be present in the farming areas. As agriculture is a hazardous occupation with limited worker access to health services and compensation, a need exists for further descriptive research in this area [Myers, 1990;Ciesielski et al, 1991;Chisholm et al, 19921. Internationally, fishing is regarded as a dangerous occupation [Hopper and Dean, 19921. In the case of Cape Town, examination of inquest data for a 5-year period indicated that most fatalities occurred whilst vessels were in the harbor and were due to falls overboard, associated with high blood alchol levels [Lerer LB-unpublished data].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of health insurance protection discourages many workers from utilizing the U.S. health care system. A study of occupational injuries among randomly selected hired farm workers in North Carolina found that among the more seriously hurt, many did not receive prompt care or never received care (14).…”
Section: Access To Health Care Servicesmentioning
confidence: 99%
“…Limited data also suggest that within agriculture, migrant, and seasonal farmworkers may be at particularly high risk for certain types of nonfatal injuries [Ciesielski et al, 1991;Isaacs and Bean, 1995;Villarejo and Baron, 1999].…”
Section: Introductionmentioning
confidence: 99%